2011
DOI: 10.1128/aac.00703-11
|View full text |Cite
|
Sign up to set email alerts
|

Zanamivir Pharmacokinetics and Pulmonary Penetration into Epithelial Lining Fluid following Intravenous or Oral Inhaled Administration to Healthy Adult Subjects

Abstract: Zanamivir serum and pulmonary pharmacokinetics were characterized following intravenous (i.v.) or oral inhaled administration. I.v. zanamivir was given as intermittent doses of 100 mg, 200 mg, and 600 mg every 12 h (q12h) for two doses or as a continuous infusion (6-mg loading dose followed by 3 mg/h for 12 h). Oral inhaled zanamivir (two 5-mg inhalations q12h for two doses) was evaluated as well. Each zanamivir regimen was administered to six healthy subjects with serial pharmacokinetic sampling. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
2
26
0
1
Order By: Relevance
“…Similarly, the concentration of zanamivir in ELF following i.v. and twice-daily oral inhalation was evaluated, and it was found that the zanamivir concentration in ELF also achieved remarkably higher values than the IC 50 s for influenza virus neuraminidases of various influenza virus subtypes, including the subtype A/H1N1, A/H3N2, and B neuraminidases (19). These data support the doses used in a phase III study to evaluate the efficacy and safety of i.v.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Similarly, the concentration of zanamivir in ELF following i.v. and twice-daily oral inhalation was evaluated, and it was found that the zanamivir concentration in ELF also achieved remarkably higher values than the IC 50 s for influenza virus neuraminidases of various influenza virus subtypes, including the subtype A/H1N1, A/H3N2, and B neuraminidases (19). These data support the doses used in a phase III study to evaluate the efficacy and safety of i.v.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, the distribution of LO and laninamivir in the lung was explored by comparison of the concentrations in the first BAL fluid and those in the remaining aliquots recovered, as performed in a study of zanamivir (19). The C max and AUC last of LO in ELF from BAL1 were 14-and 8.2-fold higher, respectively, than those for BAL2 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, following oral administration with the standard 75 mg twice-daily treatment, the average minimum plasma concentration of oseltamivir carboxylate is approximately 330 nM, which is significantly higher than the 50% inhibitory concentration for viral NA (10). Furthermore, a trial by Shelton et al (30) reported median pulmonary zanamivir concentrations of 326 ng/ml in healthy adults treated with the regular 10-mg inhaled dose. Altogether, these clinical data suggest that only important increases in IC 50 s (at least 100-fold or higher) would be associated with resistance to NAIs in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized bronchoscopy and BAL procedures have been previously described (13). In brief, subjects received the following medications prior to the bronchoscopy procedure: nebulized 0.5 mg atropine with 4% lidocaine, 1 to 2 mg of midazolam, and 25 to 75 g of fentanyl.…”
Section: Methodsmentioning
confidence: 99%